2016
DOI: 10.1111/aos.12962
|View full text |Cite
|
Sign up to set email alerts
|

Ocular blood flow in glaucoma – the Leuven Eye Study

Abstract: ABSTRACT.Purpose: Elevated intra-ocular pressure (IOP) has been identified as a major risk factor for glaucoma. Additionally, extensive literature depicts a vascular dysfunction to exist in these patients. However, a large ocular blood floworiented trial to integrate these findings in the clinical setting is lacking. This study would likely help to identify which of these vascular data can be used as a clinical tool for screening and disease stratification. Method: Prospective, cross-sectional, case-control ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 37 publications
3
67
0
Order By: Relevance
“…The results of the study are beyond our scope of discussion. Briefly, they observed that glaucoma groups had lower retro-bulbar velocities and higher retinal venous saturation compared with the healthy group, which was in line with the current literature, 3 essentially implying that vascular parameters could play a moderate role in the pathogenesis of glaucoma.…”
Section: Ocular Blood Flow In Primary Open Angle Glaucoma and Normal supporting
confidence: 80%
See 1 more Smart Citation
“…The results of the study are beyond our scope of discussion. Briefly, they observed that glaucoma groups had lower retro-bulbar velocities and higher retinal venous saturation compared with the healthy group, which was in line with the current literature, 3 essentially implying that vascular parameters could play a moderate role in the pathogenesis of glaucoma.…”
Section: Ocular Blood Flow In Primary Open Angle Glaucoma and Normal supporting
confidence: 80%
“…Altered retinal and choroidal blood flow, decreased retrobulbar velocities, and higher retinal venous saturation are some factors that have been researched upon and hypothesized to have been involved in glaucoma progression. 3 However, no study integrates all of the above or conclusively provides evidence for vascular dysfunction.…”
Section: Ocular Blood Flow In Primary Open Angle Glaucoma and Normal mentioning
confidence: 99%
“…The origin of spontaneous RVP in the eye is debated, with some researchers suggesting abnormalities in the ocular perfusion pressure in combination with high central retinal vein pressures as the main factor [3335], whereas others argue for an imbalance in translaminar pressure gradient across the lamina cribrosa (IOP-CSF pressure) [36, 37]. Lower venous pulsations are also observed in primary open angle glaucoma [38].…”
Section: Discussionmentioning
confidence: 99%
“…OCT is a useful tool for choroidal studies; nevertheless, the role of choroidal analysis for ocular pathologies is not yet established. Spectral domain-optical coherence tomography (SD-OCT), mostly with enhanced depth imaging (EDI), has been used to evaluate the macular and peripapillary choroid (mainly in healthy eyes and glaucoma patients) [12,13], but the relation of OCT measurements with changes in the peripapillary choroid remain unclear. Some studies report a reduction in the mean or regional peripapillary choroidal thickness (PPCT) in primary open-angle glaucoma [1416], but in these studies, choroidal thickness was measured manually using SD-OCT at only a few points and beneath the circumpapillary ring, an area typically used for RNFL evaluation.…”
Section: Introductionmentioning
confidence: 99%